Reforms in the Fight Against Corruption in the Republic of Uzbekistan - Nosirov Behruz Sherzodovich (Scientific Trends, 2025)
In this article, the reforms implemented in the Republic of Uzbekistan in the fight against corruption are extensively analyzed. It describes the negative impact of corruption on society, economy and state administration, the laws adopted for its prevention and elimination, state programs and their practical results. Information was also given about the activities of the Anti-Corruption Agency, the importance of ensuring transparency through the introduction of digital technologies, the open information system, the "Open Budget" platform, and the e-government system. The article also analyzes the role of civil society institutions, mass media and public control mechanisms in the fight against corruption. According to the results of the research, it was found that the ongoing reforms serve to strengthen the principles of honesty, justice and trust in public administration.
Keywords: Corruption, reforms, law, public administration, honesty, justice, transparency, Anti-Corruption Agency, e-government, open data, digital technologies,